Diagnostic Approach of Abnormal Uterine Bleeding - Riyan H. Kurniawan; St. Finekri A. Abidin (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To introduce and apply PALM-COEIN classification system as standard diagnostic approach of AUB to investigate the etiology. Method: Three cases willbe discussed. First, Mrs, 45 yo, P3with AUB due to suspected adenomiosis, perform ed total hystere ctomy with histopathology result leiomyoma. Second case. Mrs, 43 yo, P3 with AUB due to suspected adenomiosis, performed total hysterectomy with histop athology result adenomyoma. Third case, Mrs, 48 yo, P3 with AUB due to suspected adenomiosis, perform ed tot al hyst erectomy and bilateral salpingoophorectomy with PA result adenomyosis. Result: AUB diagnostic approach with PALM-COEIN performed to look for etiology and prevent mistake of etiology ofAUB, such as cancer that must be consider on AUB patient above 40 years old. Conclusion: This PALM-COEIN classification should become stan dard diagnostic appro ach to investigate the etiology. Keywords: abnormal uterine bleeding.